Factors associated with dropout during recruitment and follow-up periods of a mHealth-based randomized controlled trial for Mobile.Net to encourage treatment adherence for people with serious mental health problems - Kannisto, Kati Anneli; Korhonen, Joonas; Adams, Clive E.; Koivunen, Marita Hannele; Vahlberg, Tero; Välimäki, Maritta Anneli (JMIR Publications, 2017)
Background: Clinical trials are the gold standard of evidence-based practice. Still many papers inadequately report methodology in randomized controlled trials (RCTs), particularly for mHealth interventions for people with serious mental health problems. To ensure robust enough evidence, it is important to understand which study phases are the most vulnerable in the field of mental health care.